x/2-(x-1/3)=1/6(x+1)+1/12
Attachments:
![](https://hi-static.z-dn.net/files/d75/f5b7d63ebea915b2efec0e3c50740c36.jpg)
Answers
Answered by
5
Solution:-
given by
![\frac{x}{2} - \frac{1}{4} (x - \frac{1}{3} ) = \frac{1}{6} (x + 1) + \frac{1}{12} \\ \frac{x}{2} - \frac{x}{4} + \frac{1}{12} = \frac{x}{6} + \frac{1}{6} + \frac{1}{12} \\ \frac{6x - 3x + 1}{12} = \frac{2x + 2 + 1}{12} \\ 3x - 2x = 3 - 1 \\ (x = 2)ans \frac{x}{2} - \frac{1}{4} (x - \frac{1}{3} ) = \frac{1}{6} (x + 1) + \frac{1}{12} \\ \frac{x}{2} - \frac{x}{4} + \frac{1}{12} = \frac{x}{6} + \frac{1}{6} + \frac{1}{12} \\ \frac{6x - 3x + 1}{12} = \frac{2x + 2 + 1}{12} \\ 3x - 2x = 3 - 1 \\ (x = 2)ans](https://tex.z-dn.net/?f=+%5Cfrac%7Bx%7D%7B2%7D++-++%5Cfrac%7B1%7D%7B4%7D+%28x+-++%5Cfrac%7B1%7D%7B3%7D+%29+%3D++%5Cfrac%7B1%7D%7B6%7D+%28x+%2B+1%29+%2B++%5Cfrac%7B1%7D%7B12%7D++%5C%5C++%5Cfrac%7Bx%7D%7B2%7D++-++%5Cfrac%7Bx%7D%7B4%7D++%2B++%5Cfrac%7B1%7D%7B12%7D++%3D++%5Cfrac%7Bx%7D%7B6%7D++%2B++%5Cfrac%7B1%7D%7B6%7D++%2B++%5Cfrac%7B1%7D%7B12%7D++%5C%5C++%5Cfrac%7B6x+-+3x+%2B+1%7D%7B12%7D++%3D++%5Cfrac%7B2x+%2B+2+%2B+1%7D%7B12%7D++%5C%5C+3x+-+2x+%3D+3+-+1+%5C%5C+%28x+%3D+2%29ans)
given by
Answered by
1
Step-by-step explanation:
x/2 - ¼(x-⅓)= ¹/6(x+1)+ 1/12
=> x/2 - x/4+¹/12 = x/6 + 1/6 + 1/12
=> 6x - 3x + 1 = 2x + 3
=> 3x - 2x = 3-1
=> x = 2
Similar questions
Social Sciences,
8 months ago
India Languages,
8 months ago
Hindi,
8 months ago
Chemistry,
1 year ago
Math,
1 year ago
Geography,
1 year ago